O pedobatismo cristão: aproximações e contrastes entre o batismo Presbiteriano e o Católico Romano - Carvalho Junior, Addy (2014)
The baptism as a ritual of purification has been practiced since the older religions. With the christians, this practice becomes a ritual of iniciation in a determinate community. But, over history, also because of the appearence of lots of Christians denominations, this practice has been suffering attacks and lots of alterations. The objective of this research is make a comparative description between the infant baptism in the Roman Catholic Church and in the Presbiterian Church, emphasizing similarities and differences. We show that the pedobatism doctrin in both churchs is different, but in practice and also in the popular belief has yours similarities. We also show the need for teaching in churchs, for this Sacrament be not only applied on churchs, but for the members understand why they baptizes they children.